Design patterns (Clean Coders video series) - Martin, Robert C. (Addison-Wesley Professional, 2018)
"Get ready for something very different. This ain't no screen cast. This ain't no talkin' head lecture. This is an Uncle Bob Video! This is like watching Uncle Bob on stage, but more so. This is high content education that will hold your attention and stimulate your thoughts with its impactful and energetic style. This video collection includes episodes 25-34 from the Clean Code: Design Patterns series by Robert 'Uncle Bob' Martin."--Resource description page
Title and publication information from resource description page (Safari, viewed September 14, 2018)
Keywords: Software patterns; Computer software -- Development; Computer software -- Reliability; Logiciels; Modèles de conception; Logiciels; Fiabilité; Computer software; Development; Computer software; Reliability; Electronic videos